Management of Hermansky-Pudlak syndrome in pregnancy and review of literature. (17th November 2016) - Van Avermaete, Freya; Muys, Joke; Jacquemyn, Yves
Abstract : We report on the obstetric outcome of a woman aged 27 years with Hermansky-Pudlak syndrome (HPS). She underwent a caesarean section after failed induction of labour. Platelet transfusion was administered in a set schedule for 36 hours, starting 2 hours before delivery. The child had good Apgar scores and there were no significant problems of prolonged bleeding during the procedure. 72 hours postpartum, a haematoma developed at the site of the wound, subsequently complicated by a secondary infection for which she received antibiotics. Wound care was provided in an outpatient setting during 2 weeks, in which the infection stabilised and responded to the treatment. Mother and child could leave the hospital after 6 days.